History of registration for publication in Scotland - Ockrent, Lewis (The University of Edinburgh, 1937)
Under the above title we comprehend an enquiry dealing with the land registers only, to which the nomen juris "Registration for Publication" is technically applied. The first part of this work is devoted to a review of the factors, particularly those of a political, economic and social character, which have played their part in the process of the evolution of the various land registers of Europe and the British Isles, excluding Scotland. Though, on a strict interpretation, this may not fall within the scope of our enquiry, nevertheless we regard this preliminary survey as of some importance if the comparative standpoint is not to be ignored; furthermore, we trust that, as a result of widening our perspective, Scotland's claim of having made a distinctive contribution in this special branch of jurisprudence will be fully substantiated.
An enquiry into the history of registration for publication in Scotland